Performance of four different nanoparticles in boundary layer flow over a stretching sheet in porous medium driven by buoyancy force - Kuttan, B. Ammani; Manjunatha, S.; Jayanthi, S.; Gireesha, B. J. (Zielona Góra: Uniwersytet Zielonogórski)
This contemporary work explores the theoretical analysis of energy transfer performance of distinct nanoparticles (silver, copper, aluminium oxide and titanium oxide) adjacent to a moving surface under the influence of a porous medium which is driven by the buoyancy force. A mathematical model is presented which is converted to similarity equations by employing similarity transformation.
Keywords: natural convection; porous parameter; nanofluid; numerical solutions; volume fraction